2011
DOI: 10.1007/s10499-011-9433-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined shrimp and rice farming on water and soil quality in Bangladesh

Abstract: This study analyzed water and soil quality and environmental impacts of shrimp farming in the southwestern coastal region of Bangladesh. Shrimp farming in the region is very traditional in nature where two culture systems viz. shrimp-rice and shrimponly are being practiced, which are characterized by lower production, repeated stocking, irregular feeding, and fertilizing. Water quality in both farming systems was found suitable for optimum growth and survival of shrimp (Penaeus spp.). The level of 5-day biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…Results also revealed that S7, S8, S9, S10 & S11 shows statistically similar and result indicated plain area contain higher P content than valley area soils, as site of S1, S2, S3 & S4. Thus, Content of % of total phosphorus were very low (Tables 2 and 5) in study area according to SRDI, 2003;BARC, 2005 andChowdhury et al 2011 reported that 41% of the soils of Bangladesh contained P below the critical level and 35% of the soils contained P above the critical level but below the optimum level. The phosphorus content in soils depends largely on the application of fertilizers for agricultural practices and it present in soil as solid phase with varying degree of solubility.…”
Section: ) Total Nitrogen (N) Content (%)mentioning
confidence: 90%
See 2 more Smart Citations
“…Results also revealed that S7, S8, S9, S10 & S11 shows statistically similar and result indicated plain area contain higher P content than valley area soils, as site of S1, S2, S3 & S4. Thus, Content of % of total phosphorus were very low (Tables 2 and 5) in study area according to SRDI, 2003;BARC, 2005 andChowdhury et al 2011 reported that 41% of the soils of Bangladesh contained P below the critical level and 35% of the soils contained P above the critical level but below the optimum level. The phosphorus content in soils depends largely on the application of fertilizers for agricultural practices and it present in soil as solid phase with varying degree of solubility.…”
Section: ) Total Nitrogen (N) Content (%)mentioning
confidence: 90%
“…The pale green color of N-deficient plants is the most common deficiency symptom exhibited by growing plants (Thompson & Troeh, 1978). Optimum limit of percentage of total nitrogen (N) is four categories such as low (< 0.180%), medium (0.180-0.360%), high (0.361-0.450%) and very high (> 0.45%) (SRDI, 2003;BARC, 2005;Chowdhury, Khairun, Salequzzaman, & Rahman, 2011). Total nitrogen (%) content ranged from 0.03 to 0.12% in the study area (Tables 2 and 5).…”
Section: ) Total Nitrogen (N) Content (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…The soil quality index value was calculated using equation 1 to compare soil fertility status between the shrimp-boro rice cropping system and the aman rice-boro rice cropping system. This concept was adopted from Chowdhury, Khairun, Salequzzaman & Rahman (2011).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of higher levels of K, Ca, Mg and S in the study area soils was caused naturally. According to Chowdhury et al (2011), naturally saline water contains various dissolved solids composed mainly of carbonates, bicarbonates, chlorides, sulphates, phosphates, silica, Ca, Mg, sodium, and K. In addition to the saline water, the chemicals (Calcium carbonate and triple super phosphate) and the feedstuff (rice polish) were applied for shrimp cultivation; consist of a higher amount of K, Ca, Mg and S (Hashim, Aminuddin, & Siva, 1996) and some other chemical fertilizers were also applied in each rice growing season. These would be the cause of increasing levels of K, Ca, Mg and S in the soils of both study area cropping systems.…”
Section: Yield Amentioning
confidence: 99%